Association of Breakfast Skipping with Academic Performance among Undergraduate Students - Raza, Saad; Akhtar, Parveen; Memon, Faiza; Muhammad Rahimoon; Munwar Us Salam; Rahimoon, Ubedullah (Indus Journal of Bioscience Research, 2024)
Breakfast is said to be the most essential meal of the day for circadian rhythm and physiological metabolism. Breakfast is broadly acknowledged as a key element of a healthy lifestyle, providing essential nutrients for individuals of all age groups, including children, adolescents, and adults. Consumption of a healthy breakfast plays an essential role in various aspects of health and well-being, including academic performance. This study aims to evaluate the association of breakfast skipping with academic performance among undergraduate students. The study was conducted at the Liaquat University of Medical & Health Science (LUMHS), Jamshoro. A comparative cross-sectional study design was used and the study was conducted among Undergraduate students of 2nd year to 4th year of BS Nursing (Generic), Doctor of Pharmacy, and Doctor of Physiotherapy degree programs. A sample size of 345n was used. A stratified random sampling technique was employed. Students from Students of 2nd year to 4th year of BS Nursing (Generic), Doctor of Pharmacy, and Doctor of Physiotherapy were included whereas Students studying in 1st year were excluded. In this study, The Academic Performance Scale (APS) was used Along with the student’s last semester’s Cumulative grade point average (CGPA). Breakfast skipping was measured using questions about breakfast eating like “Do you eat breakfast”. The findings from the current study revealed a significant association was found between breakfast skipping and academic performance. Students who regularly consumed breakfast demonstrated higher academic performance However; breakfast skipping did not significantly affect cumulative GPA, indicating that while daily breakfast consumption may contribute to better academic engagement, it may not be the sole determinant of long-term academic outcomes.